Modeling both direct and indirect environmental load of purchase decisions: a web-based tool addressing household metabolism. (September 2015) - Frostell, Björn M.; Sinha, Rajib; Assefa, Getachew; Olsson, Lars E.
Abstract: Consumer awareness is continuously increasing towards pro-environmental behavior. Thus, we developed a web-based environmental feedback tool EcoRunner, which is designed for Swedish households aiming at increasing the awareness in a more pro-environmental direction. The conceptual model of EcoRunner has been developed based on top-down and bottom-up approaches connecting economic activities within a household to environmental pressures (both direct and indirect). In addition, the development of the tool includes a multi-level model aiming at better tailor-made advice to consumers. In this paper, we examine the EcoRunner tool with average single Swedish household expenditures as well as explore options for reductions and systems effects. Analysis shows that food and non-alcoholic beverages, fuel for personal transport (e.g. car) and air transports have significant environmental pressures. In addition, this study suggests that EcoRunner could be used in education systems as an environmental feedback tool to enlighten consumers motivation and change consumption patterns. Graphical abstract: Highlights: We developed a web-based environmental feedback tool aiming at increasing awareness in a more pro-environmental direction. The tool is based on top-down and bottom-up approaches to address household metabolism with environmental pressures. It offers unique possibility to get simultaneous follow-up of economic spendings and environmental pressure of a household. The tool could be used in education systems as an environmental feedback tool.